Relative fat mass and cardiovascular risk in Peruvian adults: Findings from a national survey - José A. Chaquila; Akram Hernández-Vásquez; Jamee Guerra Valencia; Fresia Miranda-Torvisco; Gianella Ramirez-Jeri (PLoS ONE, 2026)
Background In the Region of the Americas, particularly in low- and middle-income countries such as Peru, cardiovascular disease (CVD) remains one of the leading causes of mortality. A positive association has also been described between body fat percentage and CVD risk. Objective To evaluate the association between obesity, defined by Relative Fat Mass (RFM, an anthropometric indicator that estimates total body fat), and 10-year cardiovascular risk estimated by the Framingham risk score. Methods A cross-sectional study was conducted using data from the Food and Nutrition Surveillance by Life Stages survey (2017–2018) in Peru. Obesity was the exposure variable defined by RFM. The RFM was also analyzed both as a continuous and categorical variable. Generalized linear models of the gamma family with a logarithmic link were applied and stratified by sex. Results Data from 651 adults were analyzed. The prevalence of obesity was 78.2% in women and 42.7% in men. After adjusting for age, poverty, fruit and vegetable consumption, and altitude of residence, obesity defined by RFM was associated with higher estimated Framingham risk scores in both sexes (Women: β: 0.48; 95% CI: 0.32–0.63; Men: β: 0.39; 95% CI: 0.23–0.56. Similar results were observed when RFM was analyzed as a continuous variable and in tertiles. Conclusion Obesity defined by RFM was positively associated with estimated 10-year cardiovascular risk in both sexes, with stronger association in women. These results suggest that RFM may serve as a useful tool for assessing estimated 10-year cardiovascular risk, with implications for the design of public health interventions in Peru.